2009
DOI: 10.1681/asn.2008060564
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PKD Protein-Positive Exosome-Like Vesicles

Abstract: Proteins associated with autosomal dominant and autosomal recessive polycystic kidney disease (polycystin-1, polycystin-2, and fibrocystin) localize to various subcellular compartments, but their functional site is thought to be on primary cilia. PC1ϩ vesicles surround cilia in Pkhd1 del2/del2 mice, which led us to analyze these structures in detail. We subfractionated urinary exosome-like vesicles (ELVs) and isolated a subpopulation abundant in polycystin-1, fibrocystin (in their cleaved forms), and polycysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
326
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(342 citation statements)
references
References 46 publications
(54 reference statements)
14
326
0
2
Order By: Relevance
“…[1][2][3] The three proteins are found at low levels in tubular epithelial cells, but are abundant in urinary exosomes. 4,5 Polycystin-1 resembles a receptor or adhesion protein and is also found at the plasma membrane and, possibly, in the endoplasmic reticulum. [6][7][8] Polycystin-1 interacts with the inositol 1,4,5-trisphosphate receptor (IP3R).…”
Section: Disruption Of Intracellular Calcium Homeostasis and Pkdmentioning
confidence: 99%
“…[1][2][3] The three proteins are found at low levels in tubular epithelial cells, but are abundant in urinary exosomes. 4,5 Polycystin-1 resembles a receptor or adhesion protein and is also found at the plasma membrane and, possibly, in the endoplasmic reticulum. [6][7][8] Polycystin-1 interacts with the inositol 1,4,5-trisphosphate receptor (IP3R).…”
Section: Disruption Of Intracellular Calcium Homeostasis and Pkdmentioning
confidence: 99%
“…12 Consistent with a renal tubular epithelial origin, renal tubular epithelial cells contain MVBs at the apical surface, and urine exosomes contain apical membrane proteins from every cell type along the nephron. 13,14 The array of functions ascribed to exosomes in other tissues has kindled recent interest in the functional significance of urinary exosomes. Hogan et al 13 suggested interaction of exosome-like vesicles with primary cilia of renal epithelial cells, and Street and coworkers 15 showed in vitro uptake of exosomes by a renal cortical collecting duct cell line, leading to speculation that exosomes may provide intrarenal proximal-to-distal transapical renal tubular epithelial signaling through RNA transfer.…”
mentioning
confidence: 99%
“…13,14 The array of functions ascribed to exosomes in other tissues has kindled recent interest in the functional significance of urinary exosomes. Hogan et al 13 suggested interaction of exosome-like vesicles with primary cilia of renal epithelial cells, and Street and coworkers 15 showed in vitro uptake of exosomes by a renal cortical collecting duct cell line, leading to speculation that exosomes may provide intrarenal proximal-to-distal transapical renal tubular epithelial signaling through RNA transfer. However, most studies on urine exosomes to date have focused on biomarker discovery, resulting in the publication of several urine exosome protein compendia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both of the polycystin proteins in their cleaved forms have been found in urinary exosome-like vehicles that interact with the primary cilium. 12 This has been suggested as a mechanism to explain the localization of PC1 at disparate cellular locations. However, despite significant progress toward understanding the pathophysiology of ADPKD, the precise function of the polycystins, and their role in cystogenesis is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%